Atomistics of the lithiation of oxidized silicon (SiOx) nanowires in reactive molecular dynamics simulations. Issue 47 (7th November 2016) - Jung, Hyun; Yeo, Byung Chul; Lee, Kwang-Ryeol; Han, Sang Soo
Abstract : The atomistic lithiation mechanism of silicon oxides (SiO x ) is clarified using the ReaxFF reactive molecular dynamics simulation. Abstract : Although silicon oxide (SiO x ) nanowires (NWs) are recognized as a promising anode material for lithium-ion batteries (LIBs), a clear understanding of their lithiation mechanism has not been reported yet. We elucidate the lithiation mechanism of SiO x NWs at the atomic scale based on molecular dynamics (MD) simulations employing the ReaxFF reactive force field developed through first-principles calculations. SiO x NWs with crystalline Si (c-Si) core and amorphous SiO2 (a-SiO2 ) shell structures of ∼1 nm in thickness show smaller volume expansion than pristine Si NWs, as found in previous experiments. Lithiation into SiO x NWs creates two interfaces: c-Si/a-Li x Si and a-Li x Si/a-Li y SiO2 . The mobility of the latter, which is located farther toward the outside of the NW, is slower than that of the former, which is one of the reasons why the thin SiO2 layer can suppress the volume expansion of SiO x NWs during lithiation. Another reason can be found from the stress distribution, as the SiO x NWs show stress distribution different from the pristine case. Moreover, the lithiation of SiO x NWs leads to the formation of Li2 O and Li4 SiO4 compounds in the oxide layer, where several Li atoms (not a majority) in Li4 SiO4 can escape from the compound and diffuse into the c-Si, in contrast to the Li2 O case. However, Li atoms that pass through the SiO2 layer penetrate into the c-Si preferentially along the 〈110〉 or 〈112〉 direction, similar to the mechanism observed in pristine Si NWs. We expect that our comprehensive understanding of the lithiation mechanism of SiO x NWs will provide helpful guidance for the design of SiO x anodes to obtain better performing LIBs.